Proses Pembiasaan dan Peran Orang Terdekat Anak Sebagai Upaya Penanaman Nilai Agama dan Moral Pada Anak Usia Dini - Mutiara Sari Dewi (SELING: Jurnal Program Studi PGRA, 2017)
Abstract: Early childhood is a child in the age range 0-6 years who have a million potential and divided on some aspects of child development. One of the aspects of development should be developed as early as possible is an aspect of the development of religious and moral values. In providing stimulus as early build of religious and moral values in early childhood must also comply with the stages of child development, as well as the necessary role of those closest to children. One of the effects that is not appropriate stimulus which is the number of criminal acts involving children, either as victims or perpetrators.The approach used in these proceedings is a qualitative approach. Data such as the fact the impact of moral build is not appropriate, the nature of early childhood, stages of child development, the nature of the process of habituation, as well as the role of those closest to children. The data is retrieved literature study of several references were analyzed and the results are presented descriptively.The conclusions as follows. 1) The process of habituation and the role of those closest to children as to build religious values and morals in early childhood, is realized through: a) pay attention to psychological development of children, particularly adapted to the stages of child development and begins with the introduction of good and bad or moral behavior and immoral in child; b) a process of habituation as soon as in children; and c) the good cooperation between those closest to children is manifested by their mutual support habituation process applied and should have the same goals for the build of religious values and morals in children. 2) The person closest to children have an important role in the survival and success of the process of habituation, in order to achieve good results and the appropriate stages of child development.